High-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method

Through cutting and convergence testing, the ceramic-brazing interface model was constructed and replaced doped, which solved the problem of poor quality of ceramics and high-nitrogen-free magnetic steel, and achieved efficient and precise regulation of brazing material research and development.

CN119501218AActive Publication Date: 2025-02-25NORTH CHINA UNIV OF WATER RESOURCES & ELECTRIC POWER +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411565555.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-25
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

In the connection between ceramics and high nitrogen-free magnetic steel, there are problems such as excessive residual stress and difficulty in wetting the ceramics with brazing elements, resulting in poor connection quality of the brazing interface, and long research and development cycle and low efficiency of brazing materials.

Method used

By cutting the ceramic and brazing crystal models constructed from the crystal model parameters based on the cutting surface, convergence tests were performed to obtain the target surface model, the ceramic-brazing interface model was constructed, and the interface behavior was replaced, and the target solder was compared to determine the target solder.

Benefits of technology

There is no need to conduct brazing experiments and tests. Behavior comparison is carried out by building an interface model, accurately regulating the brazing components, simplifying the process, reducing manpower and material consumption, shortening the R&D cycle, and improving efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501218A_ABST
    Figure CN119501218A_ABST
Patent Text Reader

Abstract

The invention provides a high-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method which comprises the following steps: constructing a brazing filler metal crystal model and a ceramic crystal model based on brazing filler metal crystal model parameters and ceramic crystal model parameters, cutting surfaces corresponding to the ceramic crystal model and the brazing filler metal crystal model are determined, a ceramic surface model and a brazing filler metal surface model are obtained through cutting based on the cutting surfaces, convergence testing is conducted on atomic layers on the surfaces of the surface models, and a target ceramic surface model and a target brazing filler metal surface model are determined; constructing a ceramic-brazing filler metal interface model based on the target ceramic surface model and the target brazing filler metal surface model, performing structure optimization on the ceramic-brazing filler metal interface model, and performing displacement doping on the optimized ceramic-brazing filler metal interface model based on multiple second brazing filler metal components to obtain a ceramic-brazing filler metal doped interface model, and comparing the interface behaviors of the ceramic-brazing filler metal interface model and the ceramic-brazing filler metal doped interface model in multiple dimensions, and determining target brazing filler metal according to a comparison result.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of welding technology, and in particular to a method for predicting the interface behavior of high-nitrogen non-magnetic steel / ceramic heterogeneous brazing. Background Art

[0002] With the widespread application of thermoelectric conversion technology in new energy vehicles, wearable devices for space exploration and other fields in recent years, it has also received great attention from industry and academia. Due to the excellent physical and chemical properties of high nitrogen steel such as non-magneticity and high strength and the high strength and high temperature resistance of ceramics, both are excellent choices for heat sinks, so the connection research between ceramics and high nitrogen non-magnetic steel has important application value.

[0003] At present, in the connection between ceramics and high-nitrogen non-magnetic steel, since ceramics and high-nitrogen steel are two materials with large differences in physical and chemical properties, there will be problems such as excessive residual stress and difficulty for brazing elements to wet ceramics in the brazing connection, resulting in poor connection quality at the brazing interface between ceramics and high-nitrogen steel. Therefore, brazing experiments, phase characterization and mechanical properties tests are often performed to test the brazing interface behavior, and then the brazing composition is adjusted according to the test results.

[0004] However, due to the large number of experiments and tests required, a lot of manpower and material resources are consumed, resulting in a long R&D cycle for brazing materials, low R&D efficiency, and difficulty in accurately controlling the brazing material components. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide a method for predicting the interface behavior of high-nitrogen non-magnetic steel / ceramic heterogeneous brazing. The method obtains a ceramic surface model and a brazing surface model by cutting the ceramic crystal model and the brazing material crystal model constructed by the crystal model parameters based on the cutting surface, performs a convergence test to obtain the target ceramic surface model and the target brazing material surface model to construct a ceramic-brazing material interface model, and performs substitutional doping on the ceramic-brazing material interface model to obtain a ceramic-brazing material doped interface model. Finally, the interface behaviors of the ceramic-brazing material interface model and the ceramic-brazing material doped interface model are compared to determine the target brazing material. There is no need to conduct various experiments and tests such as brazing experiments, phase characterization and mechanical properties testing. By constructing an interface model to compare the interface behaviors, the brazing interface behavior of different brazing material components can be predicted, and the brazing material components can be accurately controlled according to the comparison results. At the same time, it is simple and feasible, reduces the consumption of manpower and material resources, shortens the research and development cycle of brazing materials, and improves the research and development efficiency of brazing materials.

[0006] In a first aspect, an embodiment of the present application provides a method for predicting the behavior of a high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface, the method comprising:

[0007] Acquire solder crystal model parameters corresponding to the base solder and ceramic crystal model parameters corresponding to alumina, construct a solder crystal model based on the solder crystal model parameters, and construct a ceramic crystal model based on the ceramic crystal model parameters;

[0008] Determine the cutting planes corresponding to the ceramic crystal model and the solder crystal model, respectively, and cut the ceramic crystal model and the solder crystal model based on the cutting planes to obtain a ceramic surface model and a solder surface model after cutting;

[0009] Conducting a convergence test on the atomic layers of the surfaces of the cut ceramic surface model and the solder surface model, determining a target ceramic surface model of a first target atomic layer thickness and a target solder surface model of a second target atomic layer thickness according to the convergence test results, and constructing a ceramic-solder interface model based on the target ceramic surface model and the target solder surface model; wherein the ceramic-solder interface model corresponds to a first solder component;

[0010] Structural optimization is performed on the ceramic-solder interface model to obtain the optimized ceramic-solder interface model, and substitutional doping is performed on the optimized ceramic-solder interface model based on a plurality of second solder components to obtain a plurality of corresponding ceramic-solder doped interface models; wherein the ceramic-solder doped interface model corresponds to the second solder component; and the second solder component includes a plurality of doping atoms;

[0011] The interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model are compared in multiple dimensions, and a target solder that meets preset screening conditions is determined based on the comparison results.

[0012] In a possible implementation, the solder crystal model parameters include: a hexagonal close-packed structure, a space group of R-3C, a close-packed plane of (0001), α=90°;

[0013] The ceramic crystal model parameters include: the structure is a face-centered cubic structure, the space group is FM-3M, the close-packed plane is a (111) crystal plane, α=90°.

[0014] In a possible implementation, the convergence test includes a surface energy convergence test and an atomic layer spacing convergence test, the atomic layers of the surfaces of the cut ceramic surface model and the solder surface model are subjected to a convergence test, and a target ceramic surface model with a first target atomic layer thickness and a target solder surface model with a second target atomic layer thickness are determined according to the convergence test results, including:

[0015] Performing a surface energy convergence test on the ceramic surface model after cutting based on a preset surface energy convergence formula, and / or performing an atomic layer spacing convergence test on the solder surface model after cutting based on a preset atomic layer spacing convergence formula;

[0016] In response to the surface convergence of the ceramic surface model when the atomic layer thickness of the surface is a first target atomic layer thickness, and the surface convergence of the solder surface model when the atomic layer thickness of the surface is a second target atomic layer thickness, the ceramic surface model of the first target atomic layer thickness is determined as the target ceramic surface model, and the solder surface model of the first target atomic layer thickness is determined as the target solder surface model.

[0017] In a possible implementation, the surface energy convergence formula is:

[0018]

[0019] Among them, E bulk and E slab Corresponding to the total energy of the single cell and the surface model, N bulk and N slab They correspond to the number of atoms in the single cell and the surface model, respectively, and A corresponds to the area of ​​the surface model;

[0020] And / or, the atomic layer spacing convergence formula is:

[0021]

[0022] in, and d ij They represent the distance between the i-th layer and the j-th layer before and after relaxation of the surface model, respectively.

[0023] In a possible implementation, before comparing the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions, the method further includes:

[0024] The first optimization parameters are determined based on the properties of the ceramic and the basic solder; the first optimization parameters at least include functional, pseudopotential, K-point grid, cutoff energy, maximum stress and maximum displacement; wherein the functional is GGA of PBE, the pseudopotential is an ultrasoft pseudopotential, the K-point grid is 4×4×1, the cutoff energy is 517eV, the maximum stress is 0.05GPa, and the maximum displacement is

[0025] The ceramic-solder interface model and the ceramic-solder doping interface model are structurally optimized based on the first optimization parameter to obtain the structurally optimized ceramic-solder interface model and the ceramic-solder doping interface model.

[0026] In a possible implementation manner, determining the target solder that meets the preset screening conditions according to the comparison result includes:

[0027] Determining target doping atoms that meet preset screening conditions according to the comparison results;

[0028] The solder component corresponding to the target doping atom is defined as a target solder component, and the corresponding target solder is determined based on the target solder component.

[0029] In a possible implementation, the multiple dimensions include interfacial adhesion work, charge density, differential charge density, state density and Mullikan population analysis layout number, and the interfacial adhesion work is calculated by the following calculation formula:

[0030] W ad =(E X +E y -E interface ) / A interface

[0031] Among them, W ad is the interfacial adhesion work; E X E y For separate A and B layer energies; E interface is the total energy of the interface structure; A interface is the interface area.

[0032] In a second aspect, the present application also provides a device for predicting the behavior of a high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface, the device comprising:

[0033] A construction module, used to obtain solder crystal model parameters corresponding to the basic solder and ceramic crystal model parameters corresponding to alumina, construct a solder crystal model based on the solder crystal model parameters, and construct a ceramic crystal model based on the ceramic crystal model parameters;

[0034] A cutting module, used to determine the cutting surfaces corresponding to the ceramic crystal model and the solder crystal model, respectively, and cut the ceramic crystal model and the solder crystal model based on the cutting surfaces to obtain a ceramic surface model and a solder surface model after cutting;

[0035] A testing module, used to perform a convergence test on the atomic layers of the surfaces of the cut ceramic surface model and the solder surface model, determine a target ceramic surface model of a first target atomic layer thickness and a target solder surface model of a second target atomic layer thickness according to the convergence test results, and construct a ceramic-solder interface model based on the target ceramic surface model and the target solder surface model; wherein the ceramic-solder interface model corresponds to a first solder component;

[0036] A doping module is used to perform structural optimization on the ceramic-solder interface model to obtain the optimized ceramic-solder interface model, and perform substitutional doping on the optimized ceramic-solder interface model based on a plurality of second solder components to obtain a plurality of corresponding ceramic-solder doped interface models; wherein the ceramic-solder doped interface model corresponds to the second solder component; and the second solder component includes a plurality of doping atoms;

[0037] The comparison module is used to compare the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions, and determine the target solder that meets the preset screening conditions according to the comparison results.

[0038] In a possible implementation, the solder crystal model parameters include: a hexagonal close-packed structure, a space group of R-3C, a close-packed plane of (0001), α=90°;

[0039] The ceramic crystal model parameters include: the structure is a face-centered cubic structure, the space group is FM-3M, the close-packed plane is a (111) crystal plane, α=90°.

[0040] In a possible implementation, the convergence test includes a surface energy convergence test and an atomic layer spacing convergence test; the test module is specifically used to:

[0041] Performing a surface energy convergence test on the ceramic surface model after cutting based on a preset surface energy convergence formula, and / or performing an atomic layer spacing convergence test on the solder surface model after cutting based on a preset atomic layer spacing convergence formula;

[0042] In response to the surface convergence of the ceramic surface model when the atomic layer thickness of the surface is a first target atomic layer thickness, and the surface convergence of the solder surface model when the atomic layer thickness of the surface is a second target atomic layer thickness, the ceramic surface model of the first target atomic layer thickness is determined as the target ceramic surface model, and the solder surface model of the first target atomic layer thickness is determined as the target solder surface model.

[0043] In a possible implementation, the surface energy convergence formula is:

[0044]

[0045] Among them, E bulk and E slab Corresponding to the total energy of the single cell and the surface model, N bulk and N slab They correspond to the number of atoms in the single cell and the surface model, respectively, and A corresponds to the area of ​​the surface model;

[0046] and / or,

[0047] The atomic layer spacing convergence formula is:

[0048]

[0049] in, and d ij They represent the distance between the i-th layer and the j-th layer before and after relaxation of the surface model, respectively.

[0050] In a possible implementation, the high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction device further includes:

[0051] A determination module is used to determine a first optimization parameter based on the properties of the ceramic and the basic solder before comparing the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions; the first optimization parameter at least includes a functional, a pseudopotential, a K-point grid, a cutoff energy, a maximum stress and a maximum displacement; wherein the functional is GGA of PBE, the pseudopotential is an ultrasoft pseudopotential, the K-point grid is 4×4×1, the cutoff energy is 517eV, the maximum stress is 0.05GPa, and the maximum displacement is

[0052] An optimization module is used to perform structural optimization on the ceramic-solder interface model and the ceramic-solder doping interface model based on the first optimization parameter to obtain the structurally optimized ceramic-solder interface model and the ceramic-solder doping interface model.

[0053] In a possible implementation, the comparison module is specifically used for:

[0054] Determining target doping atoms that meet preset screening conditions according to the comparison results;

[0055] The solder component corresponding to the target doping atom is defined as a target solder component, and the corresponding target solder is determined based on the target solder component.

[0056] In a possible implementation, the multiple dimensions include interfacial adhesion work, charge density, differential charge density, state density and Mullikan population analysis layout number, and the interfacial adhesion work is calculated by the following calculation formula:

[0057] W ad =(E X +E y -E interface ) / A interface

[0058] Among them, Wad is the interfacial adhesion work; E X E y For separate A and B layer energies; E interface is the total energy of the interface structure; A interface is the interface area.

[0059] In a third aspect, an embodiment of the present application provides an electronic device, comprising: a processor, a storage medium and a bus, wherein the storage medium stores machine-readable instructions executable by the processor, and when the electronic device is running, the processor communicates with the storage medium through the bus, and the processor executes the machine-readable instructions to perform the steps of the high-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method as described in any one of the first aspects.

[0060] In a fourth aspect, an embodiment of the present application provides a computer-readable storage medium, on which a computer program is stored. When the computer program is executed by a processor, the steps of the high-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method described in any one of the first aspects are executed.

[0061] The embodiment of the present application provides a method for predicting the behavior of a high-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface, which obtains the brazing material crystal model parameters corresponding to the base brazing material and the ceramic crystal model parameters corresponding to the alumina, constructs a brazing material crystal model based on the brazing material crystal model parameters, and constructs a ceramic crystal model based on the ceramic crystal model parameters, determines the cutting surfaces corresponding to the ceramic crystal model and the brazing material crystal model, respectively, and cuts the ceramic crystal model and the brazing material crystal model based on the cutting surfaces to obtain a ceramic surface model and a brazing material surface model after cutting, performs a convergence test on the atomic layers of the surfaces of the ceramic surface model and the brazing material surface model after cutting, and determines according to the convergence test results A target ceramic surface model of the first target atomic layer thickness and a target solder surface model of the second target atomic layer thickness, and a ceramic-solder interface model is constructed based on the target ceramic surface model and the target solder surface model, the ceramic-solder interface model is structurally optimized to obtain an optimized ceramic-solder interface model, and the optimized ceramic-solder interface model is substitutionally doped based on a variety of second solder components to obtain a variety of corresponding ceramic-solder doped interface models, the interface behaviors of the ceramic-solder interface model and the ceramic-solder doped interface model are compared in multiple dimensions, and the target solder that meets the preset screening conditions is determined according to the comparison results. In the present application, a ceramic surface model and a solder surface model are obtained by cutting a ceramic crystal model and a solder crystal model constructed by crystal model parameters based on a cutting surface, a convergence test is performed to obtain a target ceramic surface model and a target solder surface model to construct a ceramic-solder interface model, and the ceramic-solder interface model is subjected to substitutional doping to obtain a ceramic-solder doped interface model. Finally, the interface behaviors of the ceramic-solder interface model and the ceramic-solder doped interface model are compared to determine the target solder. There is no need to conduct various experiments and tests such as brazing experiments, phase characterization and mechanical property tests. By constructing an interface model to compare the interface behaviors, the brazing interface behaviors of different solder components can be predicted, and the solder components can be accurately controlled according to the comparison results. At the same time, the application is simple and feasible, reduces the consumption of manpower and material resources, shortens the research and development cycle of brazing materials, and improves the research and development efficiency of brazing materials.

[0062] In order to make the above-mentioned objects, features and advantages of the present application more obvious and easy to understand, preferred embodiments are specifically cited below and described in detail with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0064] Figure 1 It is a flow chart of a method for predicting the behavior of a high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface provided in an embodiment of the present application;

[0065] Figure 2 It is a schematic diagram of the structure of the solder crystal model and the ceramic crystal model;

[0066] Figure 3 is an interface schematic diagram of an undoped ceramic-solder interface model and a doped ceramic-solder doping interface model;

[0067] Figure 4 It is a schematic diagram of the interfacial adhesion work of the undoped ceramic-solder interface model and the ceramic-solder doped interface model doped with different atoms;

[0068] Figure 5 It is a schematic diagram of the charge density of the undoped ceramic-solder interface model and the ceramic-solder doped interface model doped with different atoms;

[0069] Figure 6 It is a schematic diagram of the differential charge density of the undoped ceramic-solder interface model and the ceramic-solder doped interface model doped with different atoms;

[0070] Figure 7 is a flow chart of a method for predicting high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior provided according to another embodiment of the present application;

[0071] Figure 8 is a flow chart of a method for predicting high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior provided according to another embodiment of the present application;

[0072] Fig. 9 It is a schematic diagram of the structure of a high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction device provided according to an embodiment of the present application;

[0073] Fig.10 It is a structural schematic diagram of an electronic device provided according to an embodiment of the present application. DETAILED DESCRIPTION

[0074] To make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. It should be understood that the drawings in the present application only serve the purpose of explanation and description and are not used to limit the scope of protection of the present application. In addition, it should be understood that the schematic drawings are not drawn in real proportion. The flowchart used in this application shows the operations implemented according to some embodiments of the present application. It should be understood that the operations of the flowchart can be implemented out of sequence, and the steps without logical context can be reversed in order or implemented simultaneously. In addition, those skilled in the art can add one or more other operations to the flowchart under the guidance of the content of the present application, or remove one or more operations from the flowchart.

[0075] In addition, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various configurations. Therefore, the following detailed description of the embodiments of the present application provided in the drawings is not intended to limit the scope of the application claimed for protection, but merely represents the selected embodiments of the present application. Based on the embodiments of the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application.

[0076] It should be noted that the term "comprising" will be used in the embodiments of the present application to indicate the existence of the features declared thereafter, but does not exclude the addition of other features.

[0077] Considering that steel is one of the most widely used materials in industry today, the use of nitrogen can not only replace the expensive nickel element to stabilize austenite, but also improve the strength, toughness, corrosion resistance and non-magnetic properties of steel. Its yield and tensile strength can reach more than twice that of 200 series stainless steel and 300 series stainless steel. Ceramics have many excellent physical and chemical properties such as high strength, high temperature resistance, corrosion resistance, and wear resistance, and play an extremely important role in today's development. However, the high hardness and high brittleness of ceramics make ceramic materials difficult to process, so in most cases they need to be connected with metals. With the widespread application of thermoelectric conversion technology in new energy vehicles, space exploration wearable devices and other fields in recent years, it has also received great attention from industry and academia. Due to the excellent physical and chemical properties of high nitrogen steel such as non-magnetism and high strength and the characteristics of high strength and high temperature resistance of ceramics, they are both excellent choices for heat sinks, so the connection research between ceramics and high nitrogen non-magnetic steel has important application value.

[0078] At present, in the connection between ceramics and high-nitrogen non-magnetic steel, since ceramics and high-nitrogen steel are two materials with large differences in physical and chemical properties, there will be problems such as excessive residual stress and difficulty for brazing elements to wet ceramics in the brazing connection, resulting in poor connection quality at the brazing interface between ceramics and high-nitrogen steel. Therefore, brazing experiments, phase characterization and mechanical properties tests are often performed to test the brazing interface behavior, and then the brazing composition is adjusted according to the test results.

[0079] However, due to the large number of experiments and tests required, a lot of manpower and material resources are consumed, resulting in a long R&D cycle for brazing materials, low R&D efficiency, and difficulty in accurately controlling the brazing material components.

[0080] To address this problem, the present application provides a method for predicting the interface behavior of high-nitrogen non-magnetic steel / ceramic heterogeneous brazing. The method obtains a ceramic surface model and a brazing surface model by cutting a ceramic crystal model and a brazing material crystal model constructed by crystal model parameters based on a cutting surface, performs a convergence test to obtain a target ceramic surface model and a target brazing material surface model to construct a ceramic-brazing material interface model, and performs substitutional doping on the ceramic-brazing material interface model to obtain a ceramic-brazing material doped interface model. Finally, the interface behaviors of the ceramic-brazing material interface model and the ceramic-brazing material doped interface model are compared to determine the target brazing material. There is no need to conduct various experiments and tests such as brazing experiments, phase characterization and mechanical property tests. By constructing an interface model to compare the interface behaviors, the brazing interface behavior of different brazing material components can be predicted, and the brazing material components can be accurately controlled according to the comparison results. At the same time, the method is simple and feasible, reduces the consumption of manpower and material resources, shortens the research and development cycle of brazing materials, and improves the research and development efficiency of brazing materials.

[0081] Figure 1 is a flow chart of a method for predicting the behavior of a high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface provided in an embodiment of the present application, such as Figure 1 As shown, the method for predicting the behavior of the high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface in the embodiment of the present application may specifically include the following steps:

[0082] S101, obtaining solder crystal model parameters corresponding to the basic solder and ceramic crystal model parameters corresponding to alumina, constructing a solder crystal model based on the solder crystal model parameters and constructing a ceramic crystal model based on the ceramic crystal model parameters.

[0083] S102, determining the cutting surfaces corresponding to the ceramic crystal model and the solder crystal model respectively, and cutting the ceramic crystal model and the solder crystal model based on the cutting surfaces to obtain the cut ceramic surface model and the solder surface model.

[0084] S103, performing a convergence test on the atomic layers of the surfaces of the cut ceramic surface model and the solder surface model, determining a target ceramic surface model of a first target atomic layer thickness and a target solder surface model of a second target atomic layer thickness according to the convergence test results, and constructing a ceramic-solder interface model based on the target ceramic surface model and the target solder surface model.

[0085] S104, structurally optimizing the ceramic-solder interface model to obtain an optimized ceramic-solder interface model, and performing substitutional doping on the optimized ceramic-solder interface model based on a plurality of second solder components to obtain a plurality of corresponding ceramic-solder doped interface models.

[0086] S105, comparing the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions, and determining a target solder that meets the preset screening conditions according to the comparison results.

[0087] The above-mentioned high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method obtains a ceramic surface model and a brazing surface model by cutting the ceramic crystal model and the brazing material crystal model constructed by the crystal model parameters based on the cutting surface, and performs a convergence test to obtain the target ceramic surface model and the target brazing material surface model to construct a ceramic-brazing material interface model, and performs substitutional doping on the ceramic-brazing material interface model to obtain a ceramic-brazing material doped interface model, and finally compares the interface behaviors of the ceramic-brazing material interface model and the ceramic-brazing material doped interface model to determine the target brazing material. There is no need to conduct various experiments and tests such as brazing experiments, phase characterization and mechanical properties testing. By constructing an interface model to compare the interface behavior, the brazing interface behavior of different brazing material components can be predicted, and the brazing material components can be accurately controlled according to the comparison results. At the same time, it is simple and feasible, reduces the consumption of manpower and material resources, shortens the research and development cycle of brazing materials, and improves the research and development efficiency of brazing materials.

[0088] The above exemplary steps of the embodiment of the present application are described below with reference to specific examples:

[0089] S101, obtaining solder crystal model parameters corresponding to the basic solder and ceramic crystal model parameters corresponding to alumina, constructing a solder crystal model based on the solder crystal model parameters and constructing a ceramic crystal model based on the ceramic crystal model parameters.

[0090] In the embodiments of the present application, the basic solder is the solder selected for soldering, for example, Ag (silver) solder. The types of basic solders include but are not limited to Ag-based solders. The present application describes Ag-based solder as the basic solder, but does not constitute a limitation on the basic solder. Alumina is Al 2 O 3The parameters of the solder crystal model are the parameters required to build the solder crystal model, such as the parameters required for the Ag solder crystal model, and the parameters of the ceramic crystal model are the parameters required to build the Al 2 O 3 The ceramic crystal model of the base material, that is, the parameters required for the alumina crystal model, obtains the brazing crystal model parameters corresponding to the base brazing material and the ceramic crystal model parameters corresponding to the alumina, and constructs a brazing crystal model based on the brazing crystal model parameters and a ceramic crystal model based on the ceramic crystal model parameters for subsequent processing. It should be noted that, similarly, the brazing crystal model includes but is not limited to the Ag-based brazing crystal model.

[0091] The parameters of the solder crystal model include: the structure is a hexagonal close-packed structure, the space group is R-3C, the close-packed plane is the (0001) crystal plane, α=90°; the parameters of the ceramic crystal model include: the structure is face-centered cubic structure, the space group is FM-3M, the close-packed plane is (111) crystal plane, α=90°. Among them, a, b, c represent the lattice constants of the crystal model, specifically representing the lattice spacing or side lengths in three different directions in the crystal model; α represents the angle between adjacent crystal planes or crystal axes in the crystal.

[0092] Optionally, crystal structure visualization and computational simulation software can be used to construct the solder crystal model and the ceramic crystal model. The crystal structure visualization and computational simulation software can be Materials Studio, VESTA, etc. For example, Figure 2 As shown in the figure, according to the above solder crystal model parameters and ceramic crystal model parameters, Materials Studio is used to construct Al 2 O 3 Crystal model of base material and Ag solder, Figure 2 In the figure, the left a represents the Ag solder crystal model, and the right b represents the Al 2 O 3 The crystal model is a ceramic crystal model.

[0093] It should also be noted that after the solder crystal model and the ceramic crystal model are constructed, CASTEP (Cambridge Sequential Total Energy Package, a computational simulation software) can be used to perform structural optimization on the solder crystal model and the ceramic crystal model.

[0094] S102, determining the cutting surfaces corresponding to the ceramic crystal model and the solder crystal model respectively, and cutting the ceramic crystal model and the solder crystal model based on the cutting surfaces to obtain the cut ceramic surface model and the solder surface model.

[0095] In the embodiment of the present application, the cutting surface is the cutting crystal surface selected for crystal face cutting of the crystal model, the cutting surface includes the cutting surface of the ceramic crystal model and the cutting surface of the solder crystal model, the ceramic surface model is the ceramic surface model obtained by crystal face cutting of the ceramic crystal model, the solder surface model is the solder surface model obtained by crystal face cutting of the solder crystal model, the cutting surface of the ceramic crystal model and the cutting surface of the solder crystal model constructed in step S101 are determined, and the ceramic crystal model and the solder crystal model are cut respectively based on the cutting surface, that is, the ceramic crystal model is cut based on the cutting surface of the ceramic crystal model, and the solder crystal model is cut based on the cutting surface of the solder crystal model, and finally the cut ceramic surface model and the solder surface model are obtained for subsequent processing.

[0096] It should be noted that the cutting surfaces of the present application include but are not limited to (111), (100), (0001), (010) and other surfaces. For example, the cutting surface of the ceramic crystal model is determined to be the (0001) surface, and the cutting surface of the solder crystal model is determined to be the (111) surface. The ceramic crystal model is cut on the (0001) surface, and the solder crystal model is cut on the (111) surface.

[0097] S103, performing a convergence test on the atomic layers of the surfaces of the cut ceramic surface model and the solder surface model, determining a target ceramic surface model of a first target atomic layer thickness and a target solder surface model of a second target atomic layer thickness according to the convergence test results, and constructing a ceramic-solder interface model based on the target ceramic surface model and the target solder surface model.

[0098] In the embodiment of the present application, the first target atomic layer thickness, that is, the atomic layer thickness when the surface of the ceramic crystal model converges, can also be understood as the first optimal number of atomic layers, the second target atomic layer thickness, that is, the atomic layer thickness when the surface of the solder crystal model converges, can also be understood as the second optimal number of atomic layers, the target ceramic surface model, that is, a ceramic surface model whose atomic layer thickness converges to the first target atomic layer thickness (first optimal number of atomic layers), the target solder surface model, that is, a solder surface model whose atomic layer thickness converges to the second target atomic layer thickness (second optimal number of atomic layers), the ceramic-solder interface model corresponds to the first solder component, and the atomic layer thickness of the surface of the cut ceramic surface model and the solder surface model obtained in step S102 is subjected to a convergence test to obtain a convergence test result, and the first target atomic layer thickness of the ceramic surface model and the second target atomic layer thickness of the solder surface model can be determined according to the convergence test result, and then the target ceramic surface model and the target solder surface model are determined, and a ceramic-solder interface model is constructed according to the target ceramic surface model and the target solder surface model for subsequent processing.

[0099] It should be noted that when constructing an interface model including a ceramic-solder interface model, the interface mismatch of the interface model is less than a preset mismatch threshold (eg, 5%).

[0100] S104, structurally optimizing the ceramic-solder interface model to obtain an optimized ceramic-solder interface model, and performing substitutional doping on the optimized ceramic-solder interface model based on a plurality of second solder components to obtain a plurality of corresponding ceramic-solder doped interface models.

[0101] In the embodiment of the present application, the second solder component is a preset solder component different from the first solder component, and the second solder component includes a plurality of doping atoms, and the doping atoms are atoms that are substituted for atoms in the solder of the ceramic-solder interface model. The doping atoms represent active elements, and different doping atoms represent different active elements. The plurality of doping atoms include but are not limited to Ti atoms, Zr atoms, V atoms, Hf atoms, etc.; the ceramic-solder doping interface model corresponds to the second solder component, and each ceramic-solder doping interface model corresponds to a second solder component. The ceramic-solder interface model constructed in step S103 is structurally optimized to obtain an optimized ceramic-solder interface model, and the optimized ceramic-solder interface model is substitutionally doped based on the plurality of second solder components to obtain the corresponding plurality of ceramic-solder doping interface models after substitutional doping for subsequent processing.

[0102] Optionally, based on at least one second solder component, doping atoms are used to perform substitutional doping on the solder atoms in the ceramic-solder interface model to obtain a ceramic-solder doped interface model after substitutional doping. For example, the solder is an Ag-based solder, and based on the second solder component, Ti atoms, Zr atoms, V atoms, or Hf atoms are used to perform substitutional doping on some Ag atoms in the solder in the ceramic-solder interface model to obtain a ceramic-solder doped interface model, such as Figure 3 As shown, wherein a in the figure represents an undoped ceramic-solder interface model, and b, c, d, and e in the figure represent ceramic-solder doped interface models doped with Ti atoms, Zr atoms, V atoms, and Hf atoms, respectively.

[0103] S105, comparing the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions, and determining a target solder that meets the preset screening conditions according to the comparison results.

[0104] In the embodiment of the present application, the comparison results characterize the bonding strength and electronic structure of the ceramic-solder interface model and the ceramic-solder doping interface model, and the interface behaviors of the ceramic-solder doping interface model obtained in step S104 and the ceramic-solder interface model obtained in step S103 are compared in multiple dimensions to obtain comparison results in multiple dimensions, and the target solder that meets the preset screening conditions is determined based on the comparison results. Among them, the multiple dimensions include interface adhesion work, charge density, differential charge density, state density and Mulliken population analysis (Mulliken) layout number.

[0105] It should be noted that the interfacial adhesion work is calculated by the following formula:

[0106] W ad =(E X +E y -E interface ) / A interface

[0107] Among them, W ad is the interfacial adhesion work; E X E y For separate A and B layer energies; E interface is the total energy of the interface structure; A interface is the interface area.

[0108] For example, if Figure 4 As shown in the figure, the calculation results of the interface adhesion work of the undoped ceramic-solder interface model and the ceramic-solder doped interface model doped with different atoms (Ti, Zr, V, Hf atoms) are shown. It can be seen that the interface doped with active elements (i.e., doped atoms) has improved adhesion work compared with the undoped interface, which indicates that doping with active elements can promote Ag / Al 2 O 3 The interface bonding is enhanced by Ti element (i.e. Ti atom), and the interface bonding effect is the best. After doping two Ti atoms, the interface adhesion work increases from 7.79 J / m 2 Increased to 9.22 J / m 2 , while the minimum enhancement effect of Hf element is only 8.25J / m 2 , which reflects that the activity strength of the four elements is: Ti>V>Zr>Hf. This is the comparison result of the interface adhesion work of the ceramic-solder interface model and the ceramic-solder doping interface model.

[0109] For example, Figure 5As shown in the figure, the charge density diagram of the ceramic-solder doped interface model doped with different atoms (Ti, Zr, V, Hf atoms) is shown. It can be seen that the charge density between all active elements and O atoms is much higher than the charge density between Ag atoms and O atoms, indicating that the bonding tendency of active elements and O atoms is much higher than that of Ag elements, and the bond strength of the formed chemical bond is also much stronger than that of Ag-O bonds. This is also one of the reasons why the adhesion work of the interface doped with active elements is higher than that of the undoped interface. The charge density of the active element Ti-O is Zr-O VO is Hf-O From the charge density in the figure, the activity of Ti and V is higher than that of Zr and H, and the chemical bonds formed are also stronger. This is the comparison result of the charge density of the ceramic-solder interface model and the ceramic-solder doping interface model.

[0110] Continuing, for example, Figure 6 As shown in the figure, it represents the differential charge density diagram of the ceramic-solder doping interface model doped with different atoms (Ti, Zr, V, Hf atoms). It can be seen that the blue around the active elements is heavier and faces the O atoms, which means that the active elements lose electrons and are combined with the surrounding O elements surrounded by red through electrostatic attraction. It is worth noting that the heaviest blue is around Ti and V, which means that the bond strength of Ti-O bond and VO bond is stronger. This is the comparison result of the differential charge density of the ceramic-solder interface model and the ceramic-solder doping interface model.

[0111] Optionally, the target doping atom that meets the preset screening conditions is determined based on the comparison results; the solder component corresponding to the target doping atom is the target solder component, and the corresponding target solder is determined based on the target solder component. The preset screening conditions are the screening conditions for the comparison results, the target doping atom is the best atom for substitutional doping of the solder atoms in the ceramic-solder interface model, and the target solder component is the best solder component corresponding to the target doping atom. For example, Figure 4 As shown, according to the comparison results of the interface adhesion work, it is determined that Ti>V>Zr>Hf, then the Ti atom is determined to be the best doping atom, that is, the target doping atom, and the solder component corresponding to the Ti atom is the best solder component, that is, the target solder component, that is, the solder component with the most Ti atoms is the target solder component, and the corresponding Ag-based solder is determined based on the target solder component.

[0112] The method for predicting the behavior of high-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface provided in the embodiment of the present application obtains the brazing material crystal model parameters corresponding to the base brazing material and the ceramic crystal model parameters corresponding to the alumina, constructs a brazing material crystal model based on the brazing material crystal model parameters and constructs a ceramic crystal model based on the ceramic crystal model parameters, determines the cutting surfaces corresponding to the ceramic crystal model and the brazing material crystal model, respectively, cuts the ceramic crystal model and the brazing material crystal model based on the cutting surfaces to obtain the ceramic surface model and the brazing material surface model after cutting, performs a convergence test on the atomic layers of the surfaces of the ceramic surface model and the brazing material surface model after cutting, and determines the first A target ceramic surface model of a target atomic layer thickness and a target solder surface model of a second target atomic layer thickness are provided, and a ceramic-solder interface model is constructed based on the target ceramic surface model and the target solder surface model, the ceramic-solder interface model is structurally optimized to obtain an optimized ceramic-solder interface model, and the optimized ceramic-solder interface model is substitutionally doped based on a plurality of second solder components to obtain a plurality of corresponding ceramic-solder doped interface models, the interface behaviors of the ceramic-solder interface model and the ceramic-solder doped interface model are compared in multiple dimensions, and the target solder that meets the preset screening conditions is determined according to the comparison results. The high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method of the present application obtains a ceramic surface model and a brazing surface model by cutting a ceramic crystal model and a brazing material crystal model constructed by crystal model parameters based on a cutting surface, performs a convergence test to obtain a target ceramic surface model and a target brazing material surface model to construct a ceramic-brazing material interface model, and performs substitutional doping on the ceramic-brazing material interface model to obtain a ceramic-brazing material doped interface model, and finally compares the interface behaviors of the ceramic-brazing material interface model and the ceramic-brazing material doped interface model to determine the target brazing material. There is no need to conduct various experiments and tests such as brazing experiments, phase characterization and mechanical property tests. By constructing an interface model to compare the interface behaviors, the brazing interface behavior of different brazing material components can be predicted, and the brazing material components can be accurately controlled according to the comparison results. At the same time, it is simple and feasible, reduces the consumption of manpower and material resources, shortens the research and development cycle of brazing materials, and improves the research and development efficiency of brazing materials.

[0113] Further, such as Figure 7 As shown, the convergence test includes a surface energy convergence test and an atomic layer spacing convergence test; the step S103 in the above embodiment, "convergence test is performed on the atomic layers of the surfaces of the cut ceramic surface model and the solder surface model, and a target ceramic surface model with a first target atomic layer thickness and a target solder surface model with a second target atomic layer thickness are determined according to the convergence test results", can specifically include the following steps:

[0114] S701, performing a surface energy convergence test on the ceramic surface model after cutting based on a preset surface energy convergence formula, and / or performing an atomic layer spacing convergence test on the solder surface model after cutting based on a preset atomic layer spacing convergence formula.

[0115] In the embodiments of the present application, the surface energy convergence formula is the preset surface energy convergence formula for calculation in the surface energy convergence test, the atomic layer spacing convergence formula is the preset atomic layer spacing convergence formula for calculation in the atomic layer spacing convergence test, the convergence test result is the result of the convergence test on the atomic layer of the surface, and a surface energy convergence test is performed on the ceramic surface model after cutting based on the surface energy convergence formula, and / or an atomic layer spacing convergence test is performed on the solder surface model after cutting based on the atomic layer spacing convergence formula to obtain the convergence test result for subsequent processing.

[0116] S702, in response to the surface convergence of the ceramic surface model when the atomic layer thickness of the surface is the first target atomic layer thickness, and the surface convergence of the solder surface model when the atomic layer thickness of the surface is the second target atomic layer thickness, the ceramic surface model of the first target atomic layer thickness is determined as the target ceramic surface model, and the solder surface model of the first target atomic layer thickness is determined as the target solder surface model.

[0117] In an embodiment of the present application, according to the convergence test results of step S701, it can be determined that the surface convergence of the ceramic surface model is when the atomic layer thickness of the surface is the first target atomic layer thickness, and the surface convergence of the solder surface model is when the atomic layer thickness of the surface is the second target atomic layer thickness. At this time, the ceramic surface model of the first target atomic layer thickness is determined to be the target ceramic surface model, and the solder surface model of the first target atomic layer thickness is the target solder surface model.

[0118] Among them, the surface energy convergence formula is:

[0119]

[0120] Among them, γ surf is the surface energy, that is, the free energy or excess energy per unit area of ​​the surface, E bulk and E slab Corresponding to the total energy of the single cell and the surface model, N bulk and N slab They correspond to the number of atoms in the single cell and the surface model respectively, and A corresponds to the area of ​​the surface model.

[0121] The convergence formula of atomic layer spacing is:

[0122]

[0123] Where Δd represents the atomic layer spacing, and dij They represent the distance between the i-th layer and the j-th layer before and after relaxation of the surface model, respectively.

[0124] For example, the surface energy of the ceramic surface model is calculated by the surface energy convergence formula to conduct a convergence test on the surface atomic layer thickness. According to the convergence test results, the Al 2 O 3 Surface convergence means the ceramic surface model converges. When the atomic layer thickness is 7 layers, the Ag surface converges, which means the solder surface model converges. At this time, the first target atomic layer thickness is 11, the second target atomic layer thickness is 7, and the 11-layer Al 2 O 3 The surface model is the target ceramic surface model and the 7-layer Ag surface model is the target solder surface model, and the alumina / solder interface model is the ceramic-solder interface model.

[0125] Further, such as Figure 8 As shown, before comparing the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions, the high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method of the embodiment of the present application may also include the following steps:

[0126] S801, determining a first optimization parameter based on properties of ceramics and basic solder.

[0127] In the embodiment of the present application, the first optimization parameter includes at least a functional, a pseudopotential, a K-point grid, a cutoff energy, a maximum stress and a maximum displacement; wherein the functional is GGA of PBE, the pseudopotential is an ultrasoft pseudopotential, the K-point grid is 4×4×1, the cutoff energy is 517eV, the maximum stress is 0.05GPa, and the maximum displacement is The first optimization parameter is determined based on the properties of the ceramic and the basic solder. For example, the corresponding first optimization parameter is determined based on the material properties of Al2O3 and Ag-based solder.

[0128] S802, structurally optimizing the ceramic-solder interface model and the ceramic-solder doping interface model based on the first optimization parameter to obtain the structurally optimized ceramic-solder interface model and the ceramic-solder doping interface model.

[0129] In the embodiment of the present application, the ceramic-solder interface model and the ceramic-solder doping interface model are structurally optimized based on the first optimization parameter determined in step S801 to obtain the structurally optimized ceramic-solder interface model and the ceramic-solder doping interface model.

[0130] Fig. 9 is a schematic diagram of the structure of a device for predicting the behavior of a high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface provided in an embodiment of the present application, such as Fig. 9As shown, the high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction device 900 of the embodiment of the present application may specifically include:

[0131] The construction module 901 is used to obtain the solder crystal model parameters corresponding to the basic solder and the ceramic crystal model parameters corresponding to the alumina, construct the solder crystal model based on the solder crystal model parameters and construct the ceramic crystal model based on the ceramic crystal model parameters.

[0132] The cutting module 902 is used to determine the cutting surfaces corresponding to the ceramic crystal model and the solder crystal model, respectively, and cut the ceramic crystal model and the solder crystal model based on the cutting surfaces to obtain the cut ceramic surface model and the solder surface model.

[0133] Testing module 903 is used to perform convergence test on the atomic layers of the surfaces of the cut ceramic surface model and the solder surface model, determine the target ceramic surface model of the first target atomic layer thickness and the target solder surface model of the second target atomic layer thickness according to the convergence test results, and construct a ceramic-solder interface model based on the target ceramic surface model and the target solder surface model; wherein the ceramic-solder interface model corresponds to the first solder component.

[0134] The doping module 904 is used to perform structural optimization on the ceramic-solder interface model to obtain an optimized ceramic-solder interface model, and perform substitutional doping on the optimized ceramic-solder interface model based on a plurality of second solder components to obtain a plurality of corresponding ceramic-solder doped interface models; wherein the ceramic-solder doped interface model corresponds to the second solder component; and the second solder component includes a plurality of doping atoms.

[0135] The comparison module 905 is used to compare the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions, and determine the target solder that meets the preset screening conditions according to the comparison results.

[0136] In a possible implementation, the solder crystal model parameters include: a hexagonal close-packed structure, a space group of R-3C, a close-packed plane of (0001), α=90°;

[0137] The parameters of the ceramic crystal model include: the structure is face-centered cubic structure, the space group is FM-3M, the close-packed plane is (111) crystal plane, α=90°.

[0138] In a possible implementation, the convergence test includes a surface energy convergence test and an atomic layer spacing convergence test; the test module is specifically used to:

[0139] Performing a surface energy convergence test on the ceramic surface model after cutting based on a preset surface energy convergence formula, and / or performing an atomic layer spacing convergence test on the solder surface model after cutting based on a preset atomic layer spacing convergence formula;

[0140] In response to the surface convergence of the ceramic surface model when the atomic layer thickness of the surface is the first target atomic layer thickness, and the surface convergence of the solder surface model when the atomic layer thickness of the surface is the second target atomic layer thickness, the ceramic surface model of the first target atomic layer thickness is determined as the target ceramic surface model, and the solder surface model of the first target atomic layer thickness is determined as the target solder surface model.

[0141] In a possible implementation, the surface energy convergence formula is:

[0142]

[0143] Among them, E bulk and E slab Corresponding to the total energy of the single cell and the surface model, N bulk and N slab They correspond to the number of atoms in the single cell and the surface model, respectively, and A corresponds to the area of ​​the surface model;

[0144] and / or,

[0145] The convergence formula of atomic layer spacing is:

[0146]

[0147] in, and d ij They represent the distance between the i-th layer and the j-th layer before and after relaxation of the surface model, respectively.

[0148] In a possible implementation, the high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction device further includes:

[0149] A determination module is used to determine the first optimization parameters based on the properties of the ceramic and the basic solder before comparing the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions; the first optimization parameters at least include functional, pseudopotential, K-point grid, cutoff energy, maximum stress and maximum displacement; wherein the functional is GGA of PBE, the pseudopotential is ultrasoft pseudopotential, the K-point grid is 4×4×1, the cutoff energy is 517eV, the maximum stress is 0.05GPa, and the maximum displacement is

[0150] The optimization module is used to perform structural optimization on the ceramic-solder interface model and the ceramic-solder doping interface model based on the first optimization parameter to obtain the structurally optimized ceramic-solder interface model and the ceramic-solder doping interface model.

[0151] In a possible implementation, the comparison module is specifically used to:

[0152] Determine the target doping atoms that meet the preset screening conditions according to the comparison results;

[0153] The solder component corresponding to the target doping atom is defined as the target solder component, and the corresponding target solder is determined based on the target solder component.

[0154] In a possible implementation, the multiple dimensions include interfacial adhesion work, charge density, differential charge density, state density and Mullikan population analysis layout number, and the interfacial adhesion work is calculated by the following calculation formula:

[0155] W ad =(E X +E y -E interface ) / A interface

[0156] Among them, W ad is the interfacial adhesion work; E X E y For separate A and B layer energies; E interface is the total energy of the interface structure; A interface is the interface area.

[0157] The high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction device provided in the embodiment of the present application obtains the brazing material crystal model parameters corresponding to the basic brazing material and the ceramic crystal model parameters corresponding to the alumina, constructs a brazing material crystal model based on the brazing material crystal model parameters and constructs a ceramic crystal model based on the ceramic crystal model parameters, determines the cutting surfaces corresponding to the ceramic crystal model and the brazing material crystal model respectively, and cuts the ceramic crystal model and the brazing material crystal model based on the cutting surfaces to obtain the ceramic surface model and the brazing material surface model after cutting, performs a convergence test on the atomic layers of the surfaces of the ceramic surface model and the brazing material surface model after cutting, and determines the first A target ceramic surface model of a target atomic layer thickness and a target solder surface model of a second target atomic layer thickness are provided, and a ceramic-solder interface model is constructed based on the target ceramic surface model and the target solder surface model, the ceramic-solder interface model is structurally optimized to obtain an optimized ceramic-solder interface model, and the optimized ceramic-solder interface model is substitutionally doped based on a plurality of second solder components to obtain a plurality of corresponding ceramic-solder doped interface models, the interface behaviors of the ceramic-solder interface model and the ceramic-solder doped interface model are compared in multiple dimensions, and the target solder that meets the preset screening conditions is determined according to the comparison results. The high-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction device of the present application obtains a ceramic surface model and a brazing surface model by cutting the ceramic crystal model and the brazing material crystal model constructed by the crystal model parameters based on the cutting surface, performs a convergence test to obtain the target ceramic surface model and the target brazing material surface model to construct a ceramic-brazing material interface model, and performs substitutional doping on the ceramic-brazing material interface model to obtain a ceramic-brazing material doped interface model, and finally compares the interface behaviors of the ceramic-brazing material interface model and the ceramic-brazing material doped interface model to determine the target brazing material, without the need to conduct various experiments and tests such as brazing experiments, phase characterization and mechanical property tests, etc. The brazing interface behavior of different brazing material components can be predicted by comparing the interface behaviors through constructing an interface model, and the brazing material components can be accurately controlled according to the comparison results. At the same time, it is simple and feasible, reduces the consumption of manpower and material resources, shortens the research and development cycle of brazing materials, and improves the research and development efficiency of brazing materials.

[0158] like Fig.10 As shown, an electronic device 1000 provided in an embodiment of the present application includes: a processor 1001, a memory 1002 and a bus, wherein the memory 1002 stores machine-readable instructions executable by the processor 1001. When the electronic device is running, the processor 1001 communicates with the memory 1002 through the bus, and the processor 1001 executes the machine-readable instructions to perform the steps of the high-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method as described above.

[0159] Specifically, the above-mentioned memory 1002 and processor 1001 can be general-purpose memory and processor, which are not specifically limited here. When the processor 1001 runs the computer program stored in the memory 1002, it can execute the above-mentioned high-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method.

[0160] Corresponding to the above-mentioned high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method, an embodiment of the present application also provides a computer-readable storage medium, on which a computer program is stored. When the computer program is executed by the processor, the steps of the above-mentioned high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method are executed.

[0161] Those skilled in the art can clearly understand that, for the convenience and simplicity of description, the specific working process of the system and device described above can refer to the corresponding process in the method embodiment, and will not be repeated in this application. In the several embodiments provided in this application, it should be understood that the disclosed system, device and method can be implemented in other ways. The device embodiments described above are merely schematic. For example, the division of the modules is only a logical function division. There may be other division methods in actual implementation. For example, multiple modules or components can be combined or integrated into another system, or some features can be ignored or not executed. Another point is that the mutual coupling or direct coupling or communication connection shown or discussed can be through some communication interfaces, indirect coupling or communication connection of devices or modules, which can be electrical, mechanical or other forms.

[0162] The modules described as separate components may or may not be physically separated, and the components shown as modules may or may not be physical units, that is, they may be located in one place or distributed on multiple network units. Some or all of the units may be selected according to actual needs to achieve the purpose of the solution of this embodiment.

[0163] In addition, each functional unit in each embodiment of the present application may be integrated into one processing unit, or each unit may exist physically separately, or two or more units may be integrated into one unit.

[0164] If the functions are implemented in the form of software functional units and sold or used as independent products, they can be stored in a non-volatile computer-readable storage medium that is executable by a processor. Based on this understanding, the technical solution of the present application, or the part that contributes to the prior art or the part of the technical solution, can be embodied in the form of a software product, which is stored in a storage medium and includes several instructions for a computer device (which can be a personal computer, server, or network device, etc.) to perform all or part of the steps of the deployment method described in each embodiment of the present application. The aforementioned storage medium includes: various media that can store program codes, such as USB flash drives, mobile hard drives, ROM, RAM, magnetic disks, or optical disks.

[0165] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for predicting the behavior of high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface, characterized in that: The method comprises: Acquire solder crystal model parameters corresponding to the base solder and ceramic crystal model parameters corresponding to alumina, construct a solder crystal model based on the solder crystal model parameters, and construct a ceramic crystal model based on the ceramic crystal model parameters; Determine the cutting planes corresponding to the ceramic crystal model and the solder crystal model, respectively, and cut the ceramic crystal model and the solder crystal model based on the cutting planes to obtain a ceramic surface model and a solder surface model after cutting; Conducting a convergence test on the atomic layers of the surfaces of the cut ceramic surface model and the solder surface model, determining a target ceramic surface model of a first target atomic layer thickness and a target solder surface model of a second target atomic layer thickness according to the convergence test results, and constructing a ceramic-solder interface model based on the target ceramic surface model and the target solder surface model; wherein the ceramic-solder interface model corresponds to a first solder component; Structural optimization is performed on the ceramic-solder interface model to obtain the optimized ceramic-solder interface model, and substitutional doping is performed on the optimized ceramic-solder interface model based on a plurality of second solder components to obtain a plurality of corresponding ceramic-solder doped interface models; wherein the ceramic-solder doped interface model corresponds to the second solder component; and the second solder component includes a plurality of doping atoms; The interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model are compared in multiple dimensions, and a target solder that meets preset screening conditions is determined based on the comparison results.

2. The method according to claim 1, characterized in that: The solder crystal model parameters include: the structure is a hexagonal close-packed structure, the space group is R-3C, the close-packed plane is the (0001) crystal plane, α=90°; The ceramic crystal model parameters include: the structure is a face-centered cubic structure, the space group is FM-3M, the close-packed plane is a (111) crystal plane, α=90°.

3. The method according to claim 1, characterized in that The convergence test includes a surface energy convergence test and an atomic layer spacing convergence test; the atomic layers on the surfaces of the cut ceramic surface model and the solder surface model are subjected to a convergence test, and a target ceramic surface model with a first target atomic layer thickness and a target solder surface model with a second target atomic layer thickness are determined according to the convergence test results, including: Performing a surface energy convergence test on the ceramic surface model after cutting based on a preset surface energy convergence formula, and / or performing an atomic layer spacing convergence test on the solder surface model after cutting based on a preset atomic layer spacing convergence formula; In response to the surface convergence of the ceramic surface model when the atomic layer thickness of the surface is a first target atomic layer thickness, and the surface convergence of the solder surface model when the atomic layer thickness of the surface is a second target atomic layer thickness, the ceramic surface model of the first target atomic layer thickness is determined as the target ceramic surface model, and the solder surface model of the first target atomic layer thickness is determined as the target solder surface model.

4. The method according to claim 3, characterized in that: The surface energy convergence formula is: Among them, E bulk and E slab Corresponding to the total energy of the single cell and the surface model, N bulk and N slab They correspond to the number of atoms in the single cell and the surface model, respectively, and A corresponds to the area of ​​the surface model; and / or, The atomic layer spacing convergence formula is: in, and d ij They represent the distance between the i-th layer and the j-th layer before and after relaxation of the surface model, respectively.

5. The method according to claim 1, characterized in that Before comparing the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions, the method further includes: The first optimization parameters are determined based on the properties of the ceramic and the basic solder; the first optimization parameters at least include functional, pseudopotential, K-point grid, cutoff energy, maximum stress and maximum displacement; wherein the functional is GGA of PBE, the pseudopotential is an ultrasoft pseudopotential, the K-point grid is 4×4×1, the cutoff energy is 517eV, the maximum stress is 0.05GPa, and the maximum displacement is The ceramic-solder interface model and the ceramic-solder doping interface model are structurally optimized based on the first optimization parameter to obtain the structurally optimized ceramic-solder interface model and the ceramic-solder doping interface model.

6. The method according to claim 1, characterized in that Determining the target solder that meets the preset screening conditions according to the comparison results includes: Determining target doping atoms that meet preset screening conditions according to the comparison results; The solder component corresponding to the target doping atom is defined as a target solder component, and the corresponding target solder is determined based on the target solder component.

7. The method according to claim 1, characterized in that The multiple dimensions include interface adhesion work, charge density, differential charge density, state density and Mulliken population analysis layout number, and the interface adhesion work is calculated by the following calculation formula: W ad =(E X +E y -HAVE BEEN interface ) / A interface Among them, W ad is the interfacial adhesion work; E X E y For separate A and B layer energies; E interface is the total energy of the interface structure; A interface is the interface area.

8. A device for predicting the behavior of high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface, characterized in that: The device comprises: A construction module, used to obtain solder crystal model parameters corresponding to the basic solder and ceramic crystal model parameters corresponding to alumina, construct a solder crystal model based on the solder crystal model parameters, and construct a ceramic crystal model based on the ceramic crystal model parameters; A cutting module, used to determine the cutting surfaces corresponding to the ceramic crystal model and the solder crystal model, respectively, and cut the ceramic crystal model and the solder crystal model based on the cutting surfaces to obtain a ceramic surface model and a solder surface model after cutting; A testing module, used to perform a convergence test on the atomic layers of the surfaces of the cut ceramic surface model and the solder surface model, determine a target ceramic surface model of a first target atomic layer thickness and a target solder surface model of a second target atomic layer thickness according to the convergence test results, and construct a ceramic-solder interface model based on the target ceramic surface model and the target solder surface model; wherein the ceramic-solder interface model corresponds to a first solder component; A doping module is used to perform structural optimization on the ceramic-solder interface model to obtain the optimized ceramic-solder interface model, and perform substitutional doping on the optimized ceramic-solder interface model based on a plurality of second solder components to obtain a plurality of corresponding ceramic-solder doped interface models; wherein the ceramic-solder doped interface model corresponds to the second solder component; and the second solder component includes a plurality of doping atoms; The comparison module is used to compare the interface behaviors of the ceramic-solder interface model and the ceramic-solder doping interface model in multiple dimensions, and determine the target solder that meets the preset screening conditions according to the comparison results.

9. An electronic device, characterized in that: include: A processor, a memory and a bus, wherein the memory stores machine-readable instructions executable by the processor, and when the electronic device is running, the processor and the memory communicate via the bus, and when the machine-readable instructions are executed by the processor, the steps of the high-nitrogen non-magnetic steel / ceramic heterogeneous brazing interface behavior prediction method as described in any one of claims 1 to 7 are performed.

10. A computer-readable storage medium, characterized in that: The computer readable storage medium stores a computer program, which, when executed by a processor, executes the steps of the method for predicting the behavior of a high nitrogen non-magnetic steel / ceramic heterogeneous brazing interface as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for predicting nitride of non-magnetic steel connection interface

    CN114749744A

  • Ceramic metal composite thermal protection system and brazing interface wetting and caulking behavior prediction method

    CN115889917A

  • Silver-based brazing filler metal component regulation and control method for high-nitrogen steel / tungsten alloy connection

    CN118773746A

  • Brazed structure of ceramic and metal

    JP2006327888A